A crystallographic excursion in the extraordinary world of minerals: the case of Cu‐ and Ag‐rich sulfosalts. Issue 6 (11th December 2018) - Bindi, Luca; Biagioni, Cristian
Abstract : The structural behavior of copper and silver in selected natural sulfosalts where these elements play a major role is reviewed. Abstract : Copper and silver are common constituents in natural sulfosalts and can be present as minor or major components. Owing to the different kinds of coordination they can assume, these elements give rise to a number of sulfosalts that are usually quite complex to describe from a structural point of view because of the presence of twinning, disorder, polytypism and sometimes incommensurate modulation. Moreover, it is common to find them in different, partially occupied split sites, favoring the presence of strong ionic conductivity that can be related to a number of interesting technological properties. In this regard, a series of Cu‐ and Ag‐rich sulfosalts showing an excess of these cations with respect to As, Sb and Bi is particularly interesting. Their crystal structures as well as their potential interest for materials science and solid‐state physics are outlined. Copper‐ and mixed (Cu, Ag)‐sulfosalts belonging to the wittichenite, tetrahedrite, galkhaite, routhierite and nowackiite series are discussed, together with some related compounds. Whereas in the wittichenite series Cu has either a trigonal planar or tetrahedral coordination, in members of the other series this element forms three‐dimensional tetrahedral frameworks giving rise to cavities hosting other cations and anions. More difficult is the description of Ag‐rich sulfosalts owing to the highly variable coordination environments shown by this element. Structural features of selected Ag sulfosalts together with members of the argyrodite series are discussed, highlighting the particular properties derived from the behavior of Ag.